1994
DOI: 10.1210/jcem.78.2.8106608
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-pituitary-adrenal axis dysregulation in sexually abused girls.

Abstract: Childhood sexual abuse is associated with an increased incidence of age-concurrent and adult psychopathology. Little is known, however, about the biological manifestations and sequelae of childhood sexual abuse. In this study, we characterized the hypothalamic-pituitary-adrenal axis of a self-selected sample of sexually abused and control girls recruited from a prospective longitudinal study. Plasma ACTH and total and free cortisol responses to ovine CRH (oCRH) stimulation were measured in 13 sexually abused a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
146
1
9

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(165 citation statements)
references
References 36 publications
9
146
1
9
Order By: Relevance
“…This is in accordance with findings of childhood trauma research: one of the first neuroendocrine studies in maltreated children showed that sexually abused girls with a history of depression and suicidal behavior exhibited significantly higher 24-h urinary concentrations of catecholamines and their metabolites, whereas they had similar cortisol responses to CRH injection relative to matched controls [53, 54]. A more recent study [55] revealed an asymmetry between concentrations of salivary alpha-amylase, an indicator of SNS functioning, and cortisol reactivity to a social stressor: in contrast to healthy controls, maltreated youth showed no associations between the peripheral biomarkers of the HPA axis and SNS activities.…”
Section: Neuroendocrine Responses To Early-life Stress and Adult Diseasesupporting
confidence: 90%
“…This is in accordance with findings of childhood trauma research: one of the first neuroendocrine studies in maltreated children showed that sexually abused girls with a history of depression and suicidal behavior exhibited significantly higher 24-h urinary concentrations of catecholamines and their metabolites, whereas they had similar cortisol responses to CRH injection relative to matched controls [53, 54]. A more recent study [55] revealed an asymmetry between concentrations of salivary alpha-amylase, an indicator of SNS functioning, and cortisol reactivity to a social stressor: in contrast to healthy controls, maltreated youth showed no associations between the peripheral biomarkers of the HPA axis and SNS activities.…”
Section: Neuroendocrine Responses To Early-life Stress and Adult Diseasesupporting
confidence: 90%
“…Exposure to trauma is particularly detrimental when it occurs in childhood or adolescence, disrupting numerous aspects of development in cognitive, emotional, and social domains, leading to adverse mental health and educational outcomes (Cicchetti & Toth, 1995; Koenen, Moffit, Caspi, Taylor, & Purcell, 2003) with long-term consequences for learning and memory (Teicher, Anderson, & Polcari, 2012), emotional functioning (De Bellis et al, 1994; McCrory et al, 2011; McLaughlin & Hatzenbuehler, 2009; Pollak & Sinha, 2002; Pollak, Vardi, Putzer Bechner, & Curtin, 2005), social relationships, elevated risk of re-victimization (Cole & Putnam, 1992; DiLillo, 2001; Follette, Polusney, Bechtle, & Naugle, 1996), and mental disorders (Kilpatrick et al, 2003; McLaughlin et al, 2012, 2013). …”
Section: Public Health Impact Of Traumamentioning
confidence: 99%
“…Only a limited number of studies investigated abnormalities of HPA axis regulation in subjects with an objective report of childhood trauma showing elevated salivary cortisol levels in children adopted from Romanian orphanages [9], as well as reduced basal and CRH-stimulated HPA axis activity in girls with previously reported sexual abuse [10]. Studies investigating the association between retrospective reports of childhood trauma and HPA axis activity reported increased HPA axis activation during psychosocial stress but lower basal activity in depressed women [11], while others did not detect any difference in basal cortisol secretion in nonclinical groups with versus without a history of childhood trauma [12, 13].…”
Section: Introductionmentioning
confidence: 99%